Palm Oil Mill Efluent - Zeolite Mixture Improves Acid and Base Cations in Acid Sulfate Soil - Santi, Ida Nur (JOURNAL OF TROPICAL SOILS, 2020)
Acid sulfate soil contains high acid cations. Palm oil mill effluent (POME) mixed with zeolite can increase pH of acid sulfate soil. Base cations (Ca, K and Mg) on zeolite are exchangeable with H+Â  and Al3+ ions in acid sulfate soil. The aim of this study was to investigate the effects of application of POME-zeolite mixture on acid cations of acid sulfate soil. The study was arranged in a Completely Randomized Design, with 9 treatments of POME applied on 10 kg of acid sulfate soil. Acid sulfate soil was put into 45cm x 40cm polybag. POME plus zeolite powder (60 mesh, type clinoptilolite) was applied on soil by watering evenly and incubated for 4 weeks at room temperature. The results showed that the content of acid cations of exchangeable-Al and exchangeable-H decreased by 71.21% and 27.71%, respectively after application of POME -zeolite. The application of POME without zeolite decreased the content of exchangeable-Al and exchangeable-H by 46.54% and 42.75%, respectively. Aluminium saturation has decreased after POME-zeolite application from 42.68% (high) to 8.52% (very low). Base saturation increased after application of POME-zeolite application from 17.64% (very low) to 34.88% (low). Application of palm oil mill effluent-zeolite mixture decreased acid cations in acid sulfate soil. Base saturation correlates positively to pH and cation exchange capacity and negatively correlates to Al saturation. The main factors controlling the increase of pH, base saturation and cation exchange capacity of acid sulfate soil after POME-zeolite application were the decrease of exchangeable-H, followed by exchangeable-Al and total-Fe.